Asian Christologies - George Kochuthara, Shaji (Asian Horizons, 2017)
We find various Christologies in the New Testament as well as in the tradition of the Church. Although we believe in one Jesus Christ, how this faith is experienced and articulated depends on the concrete socio-cultural contexts and worldviews. What links various Christologies and what is essential is not uniformity, but the basic faith experience that Jesus is the Christ, the Son of God and the unique mediator. We can rightly say that no dogma or theologicalphilosophical formulation has completely exhausted the inexhaustible mystery of God revealed in Jesus Christ. That is, there is possibility and need of various Christologies and this is an ongoing theological process and task.